Improved care and management of paediatric neurological patients evaluated at a paediatric Rapid Access Neurology clinic: A pilot study. (18th January 2021) - Yaworski, Amanda M; Yager, Jerome Y; Richer, Lawrence; Mailo, Janette; Rajapakse, Thilinie; Kassiri, Janani
Abstract : Aim: Referral wait times for paediatric neurological patients are increasing, leading to an increased burden on the emergency department (ED). The paediatric Rapid Access Neurology (pRAN) clinic was created for paediatric patients who are clinically stable, but require an urgent paediatric neurology consultation. The objectives were to evaluate the pathways of referral, accuracy of referring diagnoses, adherence to clinic appointments, impact of clinic visitation on ED visits and patient satisfaction. Methods: Data were collected from the pRAN clinic from March 2018 until April 2019. Information was obtained from patient charts including the referring and final diagnosis, management plan and the number of visits made to the ED before and after visiting the pRAN clinic. Results: Of the 256 referred patients, 91 met inclusion criteria. The most frequent referral diagnosis was a seizure. Referring physicians and pRAN clinic neurologists differed significantly in the level of diagnostic agreement for patients <2 years of age ( P = 0.03; 95% confidence interval (CI) −0.294, 0.373). There was a significant reduction in visits to the ED made by patients 3 months after the pRAN appointment compared with before the visit ( P < 0.001; 95% CI −0.9070, −0.4088). The majority of patients felt that the clinic had high value and were satisfied with their follow‐up plan. Conclusion: This pilot study showed that a pRAN clinic can improve the accuracy of neurological diagnoses and management, especially for children <2 years of age. In addition, pRAN clinic patients make fewer subsequent visits to the ED and express high satisfaction with their care.